Treatment Strategies for the Master Athlete With Known Arthritis of the Hip and Knee. Issue 1 (January 2016) - Straker, Jonathan Scott; Vannatta, Charles N.; Waldron, Kristen
Abstract : Hip and knee arthritis can afflict individuals who continue to pursue athletic endeavors as they age. For the master athlete, conservative treatment approaches may be preferred as an initial management strategy to minimize symptoms and promote continued participation in their chosen activity. Current literature is reviewed to provide a summary of conservative, nonpharmacologic treatment options including aspects of patient education, weight management, manual therapy, and therapeutic exercise. Mechanical measures, including bracing, footwear, and foot orthotics/insoles designed to decrease joint loading, are discussed. Biomechanical considerations for the application of gait retraining and joint unloading technology are presented.